A diversity-oriented synthesis strategy enabling the combinatorial-type variation of macrocyclic peptidomimetic scaffolds1. Issue 15 (21st April 2015) - Isidro-Llobet, Albert; Hadje Georgiou, Kathy; Galloway, Warren R. J. D.; Giacomini, Elisa; Hansen, Mette R.; Méndez-Abt, Gabriela; Tan, Yaw Sing; Carro, Laura; Sore, Hannah F.; Spring, David R.
<x xml:space="preserve">Abstract</x> Macrocyclic peptidomimetics are associated with a broad range of biological activities.